Products of Apatite-Nepheline Ore Processing in the Synthesis of Low-Modulus Zeolites - Yana A. Svakhina; Marina E. Titova; Igor N. Pyagay (Universitas Pendidikan Indonesia, 2023)
The article presented the results of studies on the production of low-modulus zeolites from two types of technogenic resources containing a sufficient amount of silicon in their composition. The raw materials were nepheline concentrate and silica gel, which are products of the processing of apatite-nepheline ore. Directly before the synthesis of low-modulus zeolites, the morphology, chemical composition, and particle size of the starting materials were analyzed. The optimal parameters for sample preparation and purification of the raw materials used were also selected. The influence of the ratio of components in the reaction mixture on the type of synthesized zeolite and its characteristics were studied. The properties of synthesized zeolites from the proposed type of raw material were compared with the properties of zeolites synthesized today using the popular technology from kaolin clay, which is currently offered as an inexpensive natural raw material.